Carbonized paramagnetic complexes of Mn (II) as contrast agents for precise magnetic resonance imaging of sub-millimeter-sized orthotopic tumors - Qin, Ruixue; Li, Shi; Qiu, Yuwei; Feng, Yushuo; Liu, Yaqing; Ding, Dandan; Xu, Lihua; Ma, Xiaoqian; Sun, Wenjing; Chen, Hongmin (Nature communications, 2022)
Paramagnetic complexes containing gadolinium ions have been widely used for magnetic resonance imaging (MRI) in clinic. However, these paramagnetic complexes pose some safety concerns. There is still a demand for the development of stable MRI contrast agents that exhibit higher sensitivity and superior functionality to existing contrast agents. Here, we develop carbonized paramagnetic complexes of manganese (II) (Mn@CCs) to encapsulate Mn 2+ in sealed carbonized shells with superhigh r 1 relaxivity. Compared to the most common clinical contrast agent Magnevist, investigations in vivo demonstrate that the Mn@CCs cross the intact blood-brain barrier of normal health mice with minor metal deposition; preferentially target the glioma tissues distribute homogeneously with high penetration in an intracranial mouse model; delineate clear tumor margins in MRIs of ultrasmall single-nodule brain tumors, and multi-nodular liver tumors. The sensitivity, accuracy and low toxicity offer by Mn@CCs provides new opportunities for early molecular diagnostics and imaging-guided biomedical applications. Improving the imaging of cancer may enhance the treatment of patients, Here, the authors develop a Mn(II) based nanoparticle contrast agent for MRI imaging and show that the nanoparticles can cross the brain barrier and image glioma cells.